PANDANGAN STEREOTIPE GENDER DALAM KERJA SAMA KELOMPOK MAHASISWA - Jocelin Gotama; Madeline Ruth Alleluya Pardede; Sri Hapsari Wijayanti (Nusantara Hasana Journal, 2025)
Gender equality and justice are still problems in society, including in the context of higher education. This research aims to reveal (a) students' views on work learning in groups of different genders; (b) gender stereotypes that arise in student teamwork; (c) efforts to minimize the development of stereotypes in the campus setting. This study uses a quantitative approach by collecting data by distributing online questionnaires (Google Form) to 102 active students from several faculties at University X in Jakarta. The questionnaire is in the form of 7 Likert scale statements with five options and two open-ended questions. The data was analyzed descriptively and quantitatively. The results of this study showed that 93% of respondents did not object to teamwork, and 48% admitted that they often feel comfortable working in teams with the opposite sex. As many as 31% of respondents disagree and tend to be neutral on the assumption that women can be more stable and flexible than men in teamwork. Similarly, 33% of respondents agreed that men have more analytical thinking skills than women in teamwork. The results of this study show that there are still gender stereotypes among university students when working in teams. The campus can make efforts as an agent of change to socialize gender equality and continue developing team-based learning (TBL) as teamwork.